Study Technology In Waters Fishing Village Togok Meskom Bengkalis Sub District Province Bengkalis Riau - Ahsanur Rizqi; Arthur Brown; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study aims to determine the construction technology, environmentally friendly fishing gear togok feasibility. The method used is a survey method. The results obtained showed that the fishing gear used in the village is very diverse Meskom both the type and size of which is Togok, Nets Gills, Gombang, Rawai, Pengerih. Togok fishing gear found in waters meskom village has a 7 wicket with a total length of 35 meters and for the length of the wicket is 5 meters. Nets will be attached to each goal. This togok fishing gear total length of 11 meters, the length of 9 meters, the length of the fish are caught 2 meters. For the opening net mouth has meshsize 3 cm, 0.5 cm bar. meshzise body 2 cm to 1 m bar. bag mesh size of 0.5 cm by 1.75 barKeywords: Togok, environmentally friendly technologies, feasibility